An 1-Aminocyclopropane-1-carboxylate (ACC) deaminase-expressing endophyte increases plant resistance to flavescence dorée phytoplasma infection. (4th March 2017) - Gamalero, E.; Marzachì, C.; Galetto, L.; Veratti, F.; Massa, N.; Bona, E.; Novello, G.; Glick, B. R.; Ali, S.; Cantamessa, S.; D'Agostino, G.; Berta, G.
Abstract: Flavescence dorée is an epidemic yellows disease of grapevine, caused by a phytoplasma (FDP), for which there is currently no cure. We assessed whether the endophyte Pseudomonas migulae 8R6, able to synthesize 1-aminocyclopropane-1-carboxylate (ACC) deaminase, can limit the phytoplasma-induced damages in periwinkle, a model plant hosting FDP. Plant protection induced by 8R6 and its mutant, impaired in ACC deaminase synthesis, was compared. Fifteen plants per treatment were used; FD infection was transmitted by grafting. Evaluation of symptoms was performed every 4 days for 40 days. The presence and the amount of FDP were assessed by nested PCR and qPCR, respectively. Images of phytoplasma inside the infected plants were obtained by transmission electron microscopy. The strain 8R6 significantly reduced the number of symptomatic plants (53% vs 93%). While the density of FDP inside the leaves was unaffected by the bacterial strains, the FDP titre was under the quantification threshold in 38% of the plants inoculated with strain 8R6. Microscopical observations showed damaged FDP cells in plants inoculated with strain 8R6. The ACC deaminase activity of the endophytic bacteria P. migulae 8R6 helps the plant to regulate the level of the stress-related hormone ethylene, leading to significantly improved resistance to phytoplasma infection.